PENINGKATAN HASIL BELAJAR SISWA MELALUI PENERAPAN ALAT PERAGA CIRCULATORY BOTTLE - Meryn Maria Ulva; Siti Nurul Hidayati (PENSA: E-JURNAL PENDIDIKAN SAINS, 2022)
This study proposed to describe the implementation of learning process, students’ responses, and learning outcomes especially in knowledge aspect using the circulatory bottle. This study used a pre-experimental with one group pretest posttest design. Samples consist of 17 students of VIII A class in SMP NU Bahrul Ulum Gresik in the Academic Year 2021/2022. The data were collected using observations, questionnaires, and tests with the instrument such as test assessment sheets, student response questionnaires, attitude, and learning implementation observation sheets. The results showed that: (a) the implementation of learning with circulatory bottle for each stage in three meetings got very good category; (b) the implementation of circulatory bottle got positive responses from students with very good category; (c) learning outcome of social attitude aspects which include cooperative, curiosity, responsibility were declared complete with good and very good predicates; (d) learning outcome in the knowledge aspect increased as evidenced by the average value of N-gain in high category. Based on these results, it can be concluded that the implementation of the circulatory bottle can increase learning outcomes.